Methods of interpretation how the Supreme Court reads the Constitution - Bloom, Lackland H., Jr. (Oxford : New York ; Oxford University Press, 2009)
This title examines the various methodologies the Supreme Court, and individual justices, have employed throughout history when interpreting the Constitution.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: United States. -- Supreme Court -- History; Judicial process -- United States; Law -- United States -- Interpretation and construction; Judicial review -- United States